Psychological interventions for adults with bipolar disorder: a systematic review and meta-analysis - Oud, Matthijs; Mayo-Wilson, Evan; Braidwood, Ruth; Schulte, Peter; Jones, Steven H.; Morriss, Richard K.; Kupka, Ralph; Cuijpers, Pim; Kendall, Tim (Royal College of Psychiatrists, 2016)
Background Psychological interventions may be beneficial for bipolar disorder. Aims Efficacy evaluation of psychological interventions for adults with bipolar disorder. Methods A systematic review of randomised controlled trials.. Outcomes were meta-analysed using RevMan and confidence assessed using the GRADE-method. Results We included 55 trials with 6010 participants. Moderate quality evidence associated individual psychological interventions with reduced relapses at post-treatment and follow-up, and collaborative care with a reduction in hospitalisations. . Low quality evidence associated group interventions with fewer depression relapses at post-treatment and follow-up, and family psycho-education with reduced symptoms of depression and mania at post-treatment. Conclusions There is evidence that psychological interventions are effective for people with bipolar disorder. Limits were the very low quality of much of the evidence and therefore inconclusive. Further research should identify the most (cost)-effective interventions for each phase of this disorder.